2013
DOI: 10.3354/ab00503
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a small HSP gene from hard clam Meretrix meretrix and its potential as an environmental stress biomarker

Abstract: Heat shock proteins (HSPs) are molecular chaperones that help organisms cope with stressful conditions. In this study, a novel small HSP (sHSP) gene was identified from the hard clam Meretrix meretrix (designated as Mm-HSP20). The full length of the cDNA is 1222 bp, consisting of a 5'-terminal untranslated region (5'UTR) of 103 bp, a 3'UTR of 565 bp, and a 522 bp open reading frame encoding a polypeptide of 173 amino acids. Sequence comparison showed that Mm-HSP20 had a moderate degree of homology to the sHSP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…Although the sHSP system is responsive to a wide spectrum of heavy metal pollutants, no study currently exists on the effects of heavy metals at a transcriptional level in sea anemones. However, our results are consistent with findings reported for the scallop Argopecten irradians [15] , in which Cd and Pb also induced the expression of HSP22 , and for the clam Meretrix meretrix [66] , in which HSP20 expression levels increased significantly after cadmium exposure. However, a recent study reported that in the clam Sinonovacula constricta [67] , Cd down-regulates the expression of a sHSP , whereas lead maintained the role of a strong inducer.…”
Section: Resultssupporting
confidence: 92%
“…Although the sHSP system is responsive to a wide spectrum of heavy metal pollutants, no study currently exists on the effects of heavy metals at a transcriptional level in sea anemones. However, our results are consistent with findings reported for the scallop Argopecten irradians [15] , in which Cd and Pb also induced the expression of HSP22 , and for the clam Meretrix meretrix [66] , in which HSP20 expression levels increased significantly after cadmium exposure. However, a recent study reported that in the clam Sinonovacula constricta [67] , Cd down-regulates the expression of a sHSP , whereas lead maintained the role of a strong inducer.…”
Section: Resultssupporting
confidence: 92%
“…In the C. sinicus transcriptome developed in this study, we identified several types of heat shock protein (HSP) genes, including HSP90, HSP70, HSP60, HSP40, and HSP10. HSP family plays an important role in thermal tolerance, which is necessary for protein folding and regulation of the heat shock response [ 26 , 27 ]. The characterization of these genes provides an opportunity to understand the molecular signals involved in the thermal tolerance of planktonic copepods and will help understand the effects of global climate change on marine species with an extensive geographical distribution range.…”
Section: Discussionmentioning
confidence: 99%
“…We detected the mRNA levels of eight genes that encode stress‐response proteins (HSPs, including HSP90A , HSP90B , HSP70 , HSP20 , and HSPA5 ) and apoptosis‐related proteins ( P53 , IAP , and FADD ), which were suggested as biomarkers for environmental stress (Zhou et al 2010; Li et al 2013; Cardoso et al 2015; Lu et al 2017). Gill samples from six clams for each treatment were used in the qPCR analysis.…”
Section: Methodsmentioning
confidence: 99%